The ritual of churching of women after childbirth in Denmark, 1500-1900 - Ahlefeldt-Laurvig, M (2019)
This thesis traces the ritual of churching of women after childbirth in Lutheran Denmark which has hitherto been marginalised in scholarship. Rooted in Levitical childbirth impurity and closely linked to the Feast of the Purification of the Virgin Mary, churching was a troublesome legacy for Lutheran reformers because initially it fell short of supporting the objective of elevating marriage as the cornerstone of society and propounding procreation as the foremost duty of virtuous mothers. Reformers solved the problem by retaining a mandatory lying-in whilst remodelling churching as a thanksgiving ritual shorn of Catholic sacramentals. Yet notions of childbirth uncleanness were not immediately eradicated, and mothers reacted by reshaping the ritual to fit with their own religiosity. The ritual of churching therefore offers fresh insight into the reception of Lutheran reform at parish level. Rediscovering the rite through hymns, sermons, clerical and legal papers, narratives and material culture, this study demonstrates that churching not only served to reintegrate the mother into Church and society after childbirth but it was also a social marker for the married mother and helped to reinforce communal bonds. For the unmarried mother, however, her route back to Church and society was through church discipline. If churching thus afforded the clergy the means to shame the unwed, a married mother could well use the rite to punish an unpopular clergyman by withholding the churching fee or behaving aggressively during the ceremony. This insight adds a new facet to the scholarship of the complex power relationship between parishioners and clergy in early modern Denmark. From the eighteenth century onwards, churching was rarely performed in urban areas. Far from becoming obsolete, however, this thesis demonstrates that rural churching continued to thrive well into the nineteenth century and, in some areas, even into the first half of the twentieth century.